The social self and social death: Rethinking reparations for genocide and crimes against humanity - Marsoobian, A.T. (Pragmatism Today, 2020)
Based on a pragmatist inspired conception of the social self, the concept of reparations for the harms of genocide is reexamined. Both Raphael Lemkin, the person who invented the term “genocide,” and Claudia Card, a philosopher who examined the evil of genocide, hold similarly expansive notions of the harms inflicted by genocidal violence. Both argued that biological death is not necessarily central to genocide. For Lemkin cultural destruction of the targeted group is just as essential as the actual killing itself. Genocide is a group crime that aims to destroy the group and all the social aspects of group identity. Card similarly sees the target of genocidal violence as the social vitality of the self. This vitality is sustained by group relations. Reparations thus need to be reconceptualize in terms of the restoration of social life of the victim group and not solely on the basis of economic losses. Examples are given for the reparation of the social vitality of communities that have suffered genocide. © 2020 Central European Pragmatist Forum. All rights reserved.
Keywords: Claudia Card; Genocide; Raphael Lemkin; Reparations; Social death; Social self; dept.phi; peer-reviewed; ⛔ No DOI found

The roman catholic church in poland after the fall of communism - Gorniak-Kocikowska, Krystyna (Occasional Papers on Religion in Eastern Europe, 2020)
Keywords: dept.phi; peer-reviewed; ⛔ No DOI found

Nature, Ethics and Gender in German Romanticism and Idealism - Harry, Chelsea C. (Idealistic Studies, 2020)
Keywords: dept.phi; peer-reviewed

The problem of evil in the Neo-Confucian context: Wang Yangming’s view on evil - Yang, Xiaomei (Asian Philosophy, 2020)
Wang Yangming believes that human nature is entirely good. A question naturally arises: where is evil from? It has been argued that Wang’s idealism gives rise to the problem of evil. I first argue that the difficulty for Wang to have a coherent account of evil can be removed when his idealism is understood in a narrow sense. Second, I offer an account of Wang’s view on evil in three steps. First, I argue that evil comes from the interaction between humans and the external world according to Wang. Second, I show that given Wang’s account of human nature with three aspects, there is no contradiction between Wang’s claim that human nature is the same in everyone and Wang’s claim about differences in our natural endowment which affect our moral practice. Third, I argue that Wang’s doctrine of non-distinction of good and evil in the original substance of human nature is uniquely Confucian. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Human nature; dept.phi; idealism; origin of evil; peer-reviewed; physical nature

Breaking the silence: Memorialization and cultural repair in the aftermath of the armenian genocide - Marsoobian, Armen T. (Mass Violence and Memory in the Digital Age, 2020)
Keywords: dept.phi

Mandate interrupted: the problematic legacy of the international criminal tribunal for the former Yugoslavia - Pettigrew, David (Washington University Global Studies Law Review, 2020)
Keywords: dept.phi; ⛔ No DOI found